Danos à saúde, sobrecarga e sofrimento no trabalho em profissionais da saúde de serviços de saúde mental - Mendes, Valentine Cogo (2023)
Health professionals who work in mental health services are exposed to situations related to organization and working conditions which can cause health damage, overload and pathogenic distress. Objective: To analyze the relationship between health damage, overload and work distress in mental health professionals. Method: Quantitative, cross-sectional and analytical study, carried out in mental health services, such as Psychosocial Care Centers and in mental health units in general hospitals in the 4th Regional Health Coordination. Health professionals who worked in those services for at least three months took part in the data collection, which took place between October 2020 and July 2021. Data collection occurred in person and online, and a questionnaire was used as a data collection instrument for personal and work characterization, the Work-Related Harm Scales, and Indicators of Work Distress and Evaluation of the Impact of Work on Mental Health Services were also used. Data were analyzed according to descriptive and inferential statistics, using statistical software. Association analyzes, using Pearson's chi-square test, and correlation, using Spearman's correlation coefficient, were performed. The internal consistency analysis was verified using Cronbach's alpha coefficient. A significance level of 5% was adopted in all analyzes (p < 0.05). Results: 141 health professionals participated in this study, predominantly females, with a mean age of 38.17 years. Professionals who used some type of medication, who practiced physical activity, had leisure activities one or more times a week and who were not away from work due to illness prevailed. There were associations between the workplace and work variables, such as training, accidents at work, and the effect factor on team functioning on the work impact scale (p<0.05). A low risk was identified for the presence of physical, psychological and social harm, a high burden on physical and mental health and on the team's functioning, a low burden on feeling overwhelmed and a low risk for work distress. There was a strong and direct correlation between social and psychological harm, between the impacts of work on physical and mental health with team functioning and feeling overwhelmed, and between mental exhaustion and feeling overwhelmed. Conclusions: There is a significant association between harm caused by work, overload felt by the team and work-related distress, which compromises physical and mental health of mental health professionals. Contributions: this study identified associations between variables that may have a negative impact on the health of mental health professionals, an incipient scenario for investigations on workers' health. It has potential for innovation insofar as it provides data that can contribute to the planning of actions aimed at the care and promotion of health of professionals. Furthermore, it may contribute to broaden the discussions between managers and professionals, with hopes to make them aware of the health risks related to work, such as overload, distress and physical and psychosocial damage.